Sueria laxinervis, a new fossil species of Cycadales from the Upper Cretaceous Quiriquina Formation in Cocholgüe, Bíobío Region, Chile - Yamada, Toshihiro; Yamada, Takae F.; Terada, Kazuo; Ohsawa, Takeshi A.; Yabe, Atsushi; Legrand, Julien; Uemura, Kazuhiko; Leppe, Marcelo; Hinojosa, Luis Felipe; López-Sepúlveda, Patricio; Nishida, Harufumi (Phytotaxa, 2019)
A new fossil cycad species, Sueria laxinervis, is described from the Upper Cretaceous (Maastrichtian) Quiriquina Formation in Cocholgüe, Bíobío Region, Chile. The generic assignment is supported by the taeniopterid-type leaf with haplocheilic stomata and sinuate anticlinal walls of leaf epidermal cells, while S. laxinervis clearly differs from the other two described Sueria species in its sparse veins and large epidermal cells. The vascular bundles of the midrib are arranged in an inverted-omega shape, supporting the placement of Sueria in Cycadales.